Students Perception on Using Video Recording to Improve Their Speaking Accuracy and Fluency - Rosevinda Nabila Putri; Bita Dwi Rahmani (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
The aim of this study is to explore the students’ perceptions of using video recording to improve speaking accuracy and fluency of thirty-five pre-service teacher at University of Muhammadiyah Prof. Dr. Hamka Jakarta. This study employed mixed method to analyze the data. A pre-test and post-test were obtained as the instruments and analyzed quantitatively by using paired t-test. It is used to determine the students’ speaking ability before and after implementing video recording in speaking class. In qualitative method acquired a structured interview to gain their perceptions on using video recording. The results revealed a significant increase in students' speaking abilities, particularly in their accuracy and fluency. The students also show a good perception in the use of video recording in speaking classes. They stated that video recording is an interesting thing that can be used to train their speaking skills. Therefore, it is suggested that video recording might be an alternative medium for teachers or lecturers in teaching speaking. Keyword: Students’ perception, Video recording, Speaking Accuracy, Speaking Fluency.